An Evaluation of Hemostatic Abnormalities in Patients With Hemophilia According to the Activated Partial Thromboplastin Time Waveform. (October 2018) - Katayama, Haruna; Matsumoto, Takeshi; Wada, Hideo; Fujimoto, Naoki; Toyoda, Junki; Abe, Yasunori; Ohishi, Kohshi; Yamashita, Yoshiki; Ikejiri, Makoto; Habe, Koji; Katayama, Naoyuki
The usefulness of the waveform of activated partial thromboplastin time (APTT) in various diseases has been evaluated in recent years. The APTT waveform was examined in patients with hemophilia and patients positive for lupus anticoagulant (LA). The correlation with the FVIII activity was highest for the height of acceleration peak. The peak time of acceleration, velocity, and ½ fibrin formation, and the width of acceleration and velocity were significantly long and the height of acceleration was significantly low in patients with hemophilia. The height of velocity was significantly low in patients with hemophilia with inhibitor. There were no significant differences in the APTT waveform between patients with hemophilia and patients with LA, but the peak of acceleration and ½ fibrin formation were significantly longer and the height of acceleration and velocity were significantly lower in patients with hemophilia with inhibitor than in the patients with LA. Wave changes in the APTT were observed in all 22 patients positive for LA, while a biphasic waveform was observed in patients with hemophilia with FVIII activity <10.0%. The APTT waveform is useful for the analysis of hemostatic abnormalities in patients with hemophilia.